PERANCANGAN PENGELOLAHAN DATA LULUSAN BERBASIS WEB DENGAN METODE FREAMWORK CODEIGNITER DI SMK TEXAR KLARI KARAWANG - Thoyib, Imam Nurhuda; Huda , Baenil; Hananto, Agustia; Elfinanovalia , Elfinanovalia (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Along with the development of technology for web-based applications, there are many things that can be done and convenience that can be obtained through internet technology, for example, designing websites to improve information technology in junior high school institutions. Website technology is a new way of facilitating the process of conveying information which has logical consequences. The administrative part of Texar Klari Karawang Vocational School for graduate data collection information systems is still done manually by filling in data in the ledger. and filling in the data in this ledger is done when graduates/alumni want to legalize their diplomas. and after filling in the data is complete, then the officer transfers the data to a computer using Microsoft Excel. This prompted the researcher to design a graduate data management system which would later make it easier for TU officers to look up graduate data later, collect data by conducting direct interviews with relevant parties to obtain information and collect data in detail when all new data has been collected Researchers designed a data management system. researchers use the CodeIgniter programming language framework, in conclusion by carrying out several page trials of system functions, in using this system it is required to log in authentically so that it is given to be able to access and enter the system, with that a truly valid system is needed so that users can use the system properly and from the results of tests that have been carried out on several pages available inside, it is obtained with a value of 100 and there is also a value of 50 because the graduate menu is not perfect enough.